Socio-Spiritual Dimensions and Principles of Islamic Economic Law in Guidance of Pilgrims of the Wadi Fatimah Hajj Guidance Group Cirebon - Muamar, Afif; Pangestu, Muhammad Feby Ridho (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze the spiritual motives of pilgrims as a driver of innovation in hajj guidance, the transformation of the meaning of hajj through the internalization of Sharia socio-economic values, and the integration of a holistic community-based hajj guidance model in the Wadi Fatimah Cirebon Hajj Guidance Group. This study uses an interpretive qualitative approach to understand the social and spiritual experiences of pilgrims in the Wadi Fatimah Cirebon Hajj Guidance Group. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model to capture the meaning, patterns, and relationships between social, spiritual, and legal aspects in hajj practice. The study finds that: (1) the spiritual motives of pilgrims in Wadi Fatimah are driven by personal awareness rather than social pressure or status seeking, with the group playing a key role in integrating maqāṣid al-syarī‘ah and Islamic economics, supported by ethical governance and community empowerment; (2) The meaning of hajj has evolved from being a ritual to a social practice, with the group fostering both spiritual piety and socio-economic awareness through Sharia values and collaboration with state law; (3) The effectiveness of hajj guidance lies in its ability to build a holistic institutional model responsive to social dynamics. Wadi Fatimah successfully integrates spirituality, education, economic literacy, and social networks to bridge maqāṣid al-syarī‘ah with state regulations.Keywords: Socio-Spiritual Dimension; Hajj Worship; Hajj Guidance Group; Muamalah; Maqāṣid al-Syarī‘ah